Analysing rice (Oryza sativa L.) production trends—area harvested, quantity and yield stability in Tanzania - Aneth Japhet Magubika; Francis Kloh Fukah; Eliakira Kisetu Nassary; George Muhamba Tryphone (Discover Agriculture)
Abstract This study examined the trends in rice (Oryza sativa L.) production and yield stability in Tanzania, with a focus on harvested area, total production, and yield per unit land area. We utilized data from FAOSTAT ( https://www.fao.org/faostat/en/#home ), focusing on the "Production Domains (Crop and Livestock Products)" for the "United Republic of Tanzania." Filters were applied for "Area harvested," "Yield," and "Production Quantity" under "Items (Crops, Primary)" for the period 2000–2022. Other data and information were obtained from literature and government official reports. Mixed statistical analyses (Univariate and Multivariate) were performed. The univariate was performed to assess harvested area, total production, and grain yield through descriptive statistics, while multivariate analysis examined relationships among these variables and yield stability using Generalized Linear Models (GLMs) and Principal Component Analysis (PCA). The results revealed a significant increase in the area harvested, peaking at 481,000 hectares in 2020, compared to 250,000 hectares in 2000. Yield fluctuations were notable, with a significant decline in 2008 (− 729.29 kg ha⁻1) followed by a recovery in 2018 (791.28 kg ha⁻1). A strong positive correlation was confirmed between harvested area and production (0.00035791) and yield (0.0013233). PCA results demonstrated that the first three principal components accounted for 87% of the total variance. Statistical tests showed substantial yield differences between 2000 and 2010, reaching 720,690.1 kg ha⁻1, with yield stability between 2021 and 2022 noted, resulting in a minor difference of 18,802.6 kg ha⁻1. The findings reveal that harvested area significantly affects rice production, but yield variability remains a challenge. While expanding cultivated areas has increased output, yield stability is a concern. This emphasizes the need for targeted strategies to optimize cultivation and enhance food security amid changing agricultural conditions. Graphical Abstract